Are the 50 m Race Segments Changed From Heats to Finals at the 2021 European Swimming Championships? - Arellano, Raúl; Ruiz-Navarro, Jesús J.; Barbosa, Tiago M.; López-Contreras, Gracia; Morales-Ortíz, Esther; Gay, Ana; López-Belmonte, Óscar; González-Ponce, Ángela; Cuenca-Fernández, Francisco (Frontiers in Physiology, 2022)
This study explored in the 50m races of the four swimming strokes the performance parameters and/or technical variables that determined the differences between swimmers who reach the finals and those who do not. A total of 322 performances retrieved from the 2021 Budapest European championships were the focus of this study. The results of the performances achieved during the finals compared to the heats showed that the best swimmers did not excel during the heats, as a significant progression of performance was observed in most of the strokes as the competition progressed. Specifically, combining men and women, the swimmers had in freestyle a mean coefficient of variation (CV) of ~0.6%, with a mean range of performance improvement (∆%) of ∆= ~0.7%; in breaststroke a mean CV of ~0.5% and ∆= -0.2%; in backstroke a mean CV of ~0.5% and ∆= -0.6%, and; in butterfly a mean CV of ~0.7% and ∆= -0.9%. For all strokes, it was a reduction of the underwater phase with the aim of increasing its speed. However, this result was not always transferred to the final performance. In any case, most of the swimmers tried to make improvements from the start of the race up to 15m. Furthermore, the swimmers generated an overall increase in stroke rate as the rounds progressed; however, a decrease in stroke length resulted and, this balance appeared to be of little benefit to performance.